Interstitial Lung Disease after Pleurodesis for Malignant Pleural Effusion - Yokoe, Norihito (Intern Med, 2017)
OBJECTIVE: Pleurodesis is an effective therapy for malignant pleural effusion (MPE). While interstitial lung disease (ILD) has been regarded as a serious complication of pleurodesis, its clinicopathological characteristics have not been fully understood. This study was conducted to elucidate the incidence of ILD and the risk factors for ILD in patients who underwent pleurodesis to control MPE. METHODS: The medical records of patients who underwent pleurodesis in Aichi Medical University between March 2008 and February 2013, the period before the approval of talc in Japan, were retrospectively analyzed. RESULTS: A total of 84 patients underwent pleurodesis, all using OK-432. ILD occurred in 13 patients (15.5%). The development of ILD after pleurodesis was significantly associated with old age (odds ratio [OR]: 4.82, 95% confidence interval [CI]: 1.22-19.08) and epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) treatment (OR: 5.97, CI: 1.7-20.9). A multivariate analysis revealed that >67 years of age (p=0.01) and EGFR-TKI treatment (p=0.02) were significantly associated with the development of pleurodesis-related ILD. Among the patients who received both pleurodesis and EGFR-TKIs (n=23), 8 patients developed ILD. All of these patients were receiving EGFR-TKI therapy at the time of pleurodesis or within 30 days after pleurodesis. In contrast, no cases of ILD were observed among the patients who stopped EGFR-TKIs before pleurodesis or started EGFR-TKIs at more than 30 days after pleurodesis. CONCLUSION: ILD seemed to be a frequent complication of pleurodesis in patients using OK-432, especially elderly patients and those who underwent pleurodesis while receiving EGFR-TKI therapy or who started EGFR-TKI therapy within 30 days after pleurodesis.